LANJUT USIA: ANTARA TUNTUTAN JAMINAN SOSIAL DAN PENGEMBANGAN PEMBERDAYAAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Social service and social security for elderly in 2010 only covered143.131 person (Direktorat PSLU, 2010) from expectation to serve2,4 million elderly, whether it is poor and neglectedelderly (BPS, 2010). Government capacity to servesocial serviceand social security is limited, soit needsa new strategy to keepthe sustainability of elderly's life. We must have alternative way to assist them to solve their psychosocial and physical vulnerability through empowerment scheme. The psychosocial vulnerability of elderly is vulnerability that comprisefrom economic,social and psychological aspectssothat it needs comprehensive under standing to makeaprogram for them. Empowering the elderly will create activity that will be advantageousfor them to use the leisure, create social relationship, decreasefelt of loneliness, keepreciprocity relationship with their social environment, increase income, keepself existenceand build theelderly capacity. Developing empowermenthasto consider some aspects suchas environment characteristic, social-demographicstructure and multi generation.Alternative for empowermentprogram to through productive activity (carehousing and non-care housing) and social activity (volunteer). Keyword: elderly, social security, empowerment, psychosocial vulnerability